Whither and Whence Hong Kong Migration Studies?. (15th April 2013) - Bailey, Adrian J.; Alex Lau, K. L.
Abstract On 1 July 2012, Hong Kong (HK) celebrated the 15th Anniversary of its change of sovereignty to the People's Republic of China (PRC). During this period, migration has diversified greatly. Various new visa categories have been created. People from Mainland China and the rest of the world come to HK for work and settlement and HK people have gone to Mainland and overseas to study and work. To appreciate and better plan the growing diversity of migration to, from, and through HK, this article benchmarks the current legal categorizations of migration and calls for the development of a coherent theoretical approach that can better harmonize research and policy. We believe a transdisciplinary view can help generate the range of evidence needed to plan for diversity, and that this is best coordinated through a new HK Migration Observatory.